Analysis and Optimization of Motion Coupling for the Coordinated Operation of Flexible Multi-Arm Space Robots - Guangtang Pan; Qingxuan Jia; Gang Chen; Yifan Wang; Fenglei Sun (Actuators, 2023)
This paper presents a novel approach for analyzing and optimizing motion coupling in the coordinated operation tasks of flexible space multi-arm robots (FMSRs). The method integrates motion coupling between multiple arms and system stiffness to improve the motion and force accuracy of FMSRs by optimizing the configuration. First, a comprehensive model of an FMSR is established using the hypothetical modal method. Then, the motion coupling relationship among multiple arms is analyzed, and a motion coupling degree evaluation index is developed. Furthermore, the constraint relationship of coordinated operation is analyzed, and an equivalent stiffness model for the coordinated operation of the FMSR is formulated along with a stiffness evaluation index. Based on these analyses, the motion trajectory of the FMSR is optimized by comprehensively considering both the motion coupling degree and the equivalent stiffness factors. Finally, numerical simulation experiments are conducted to validate the proposed method, and the results show that the accuracy of the FMSR can be improved by 40% using this approach.